The integration of anthracyclines in the treatment of advanced ovarian cancer. (1st July 2001) - Lück, H.-J.; Du Bois, A.; Weber, B.; Pfisterer, J.; Goupil, A.; Kuhn, W.; Barats, J. C.; Blohmer, J.; Mousseau, M.; Schröder, W.; Meier, W.; Möbus, V.; et al.
Abstract : Since the publication of the Gynecologic Oncology Group (GOG) protocol 111 in 1996, and the results of the Arbeitgemeinschaft Gyna kologische Onkologie (AGO) trial Ovar-3 and the GOG protocol 158, the combination of platinum and paclitaxel has been adopted as the standard therapy in advanced ovarian cancer. One option for achieving further progress in the first-line treatment of advanced ovarian cancer might be the addition of noncross-resistant drugs to the two-drug regimen. Meta-analysis showed a survival benefit for platinum-anthracycline based combinations as compared to platinum-based combinations without anthracyclines. An AGO phase I/II trial compared epirubicin in combination with carboplatin and paclitaxel in untreated patients with gynecological malignancies. Based on the results of this study a randomized phase III trial together with the French GINECO group was conducted. The trial started 11/97 and was closed 11/99. All 1281 patients were randomized. Currently, 1132 end-of-therapy reports have been issued. Nine hundred eighty nine (87%) patients completed six cycles of treatment. Treatment and toxicity data are available for these patients. Three hundred thirty five patients had a measurable residual tumor after initial debulking surgery. Response data of 228 patients (111 ET-Carbo, 117 Carbo-T) are available.